Towards an ink-based method for the deposition of ZnxCd1-xS buffer layers in CZTS solar cells - Congiu, Mirko; Bonomo, Matteo; di Girolamo, Diego; Graeff, Carlos F. O. [UNESP]; Malerba, Claudia; Valentini, Matteo; Mittiga, Alberto; Dini, Danilo (Springer Nature, 2020)
This work explores two different deposition methods to grow buffer layers of ZnxCd1−xS for application in kesterite (Cu2ZnSnS4 (CZTS)) solar cells. The introduction of the mixed sulfide of Cd and Zn in CZTS based solar cells represents an important progress due to the improved device performance and minor toxicity with respect to sole CdS. The explored techniques are the chemical bath deposition (CBD) and the precursor ink. For the CBD we focused on the inclusion of zinc into the buffer, i.e. the target solid solution, taking into account the difference in the solubilities of ZnS and CdS. In aqueous solutions the co-deposition process is controlled by various solubility equilibria with CdS precipitation representing the most favorable process. Under these circumstances the ink method here proposed is a promising approach since it is based on the thermal degradation of stable chemical precursors deposited on a dry film. In doing so, the problematic co-deposition of a mixed sulfide derived from sulfides with considerably different solubilities is circumvented. The most important advantages of this approach are the easiness and scalability of the whole process and the reduction of the amounts of toxic reagents/products.